Prevalence of Sex Work in the Chippewa Valley : Preliminary Research - Frey, Liana; Gleason, Ann; Johnson, Nikki; Laube, Jenna; Schmitt, Crystal; Switters, Kelsey (My University, 2012)
The aim of this study was to find out the prevalence of different types of sex work and prostitution in the Chippewa Valley, while also addressing HIV/AIDS prevention efforts.
Color poster with text and images.
Keywords: Sex-oriented businesses--Wisconsin--Chippewa River Valley; Prostitution--Wisconsin--Chippewa River Valley; Chippewa River Valley (Wis.); HIV infections--Prevention; AIDS (Disease)--Prevention; Posters